Análise do tratamento endodôntico "in vitro", realizado pelos alunos da disciplina de endodontia I da Faculdade de Odontologia da Universidade Federal do Espírito Santo, utilizando-se a técnica de diafanização - Dessaune Neto, Nilton (2011)
The aim of this study was to evaluate, using the clearifying technique, the quality in vitro of the root canal therapy of teeth prepared by students of the Endodontic Class from the fifth period of the Dentistry Course. There, the students learn all the subjects involving the root canal therapy: morphology, coronary access, instrumentation techniques, disinfection and obturation. They work in extracted teeth in the University laboratories before going to clinics in the next period. This research, also aims for the evaluation of the instrumentation technique with the best results, the efficacy of the X ray as a method to evaluate the result of the treatment and if the students are prepared to clinical treatment. The Binomial Test was used to statistics. The results showed that the formatting of the root canal system was satisfactory with 67% of positive results and 33% of negative results, and with significant statistics (0,014) (p < 0,05). The conclusion of this research was that the students learned the contents of the discipline and are capable to do the root canal therapy in vivo in the sixth period, although it is necessary more practical time in the in vitro treatment to increase the accuracy of the root canal therapy. The X ray was not a good way to show the students the result of the treatment. Although the clearifying technique was an excellent method of learning the anatomy and the in vitro root canal therapy, being necessary to improve the clinical knowledge of the students.